2023
DOI: 10.3390/educsci13070742
|View full text |Cite
|
Sign up to set email alerts
|

The Task-Based Approach to Teaching Critical Thinking for Computer Science Students

Abstract: Critical thinking (CT) is one of the most important 21st-century skills that employers believe will grow in prominence. However, many higher education (HE) graduates often lack it. This is also true for graduates in computer science (CS) and related disciplines, who need CT to drive social and organizational digitalization. There are a number of strategies for teaching CT. However, there is no evidence regarding how to effectively teach CT in CS. To address this gap, this study proposes an educational approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…All this is consistent with the previous studies conducted in languages learning and other subjects. (Zhou, et al, 2013) (Ikhsan, 2020 (Mäkiö & Mäkiö, 2023) (Costa, 2016) All these findings support the formative nature of TBL in all subjects, provided by a carefully selected tasks that orientate students to the main goals of the subjects and incorporate the little details needed to carry out the assignments. Working in groups is beneficial for discussing the various approaches that can be taken into conducting the tasks and provides a well distributed task vs. material and time management ratio.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…All this is consistent with the previous studies conducted in languages learning and other subjects. (Zhou, et al, 2013) (Ikhsan, 2020 (Mäkiö & Mäkiö, 2023) (Costa, 2016) All these findings support the formative nature of TBL in all subjects, provided by a carefully selected tasks that orientate students to the main goals of the subjects and incorporate the little details needed to carry out the assignments. Working in groups is beneficial for discussing the various approaches that can be taken into conducting the tasks and provides a well distributed task vs. material and time management ratio.…”
Section: Discussionmentioning
confidence: 65%
“…As other studies on TBL had shown (Mäkiö & Mäkiö, 2023) (Al Kandari & Al Qattan, 2020, by conducting tasks students learning easier and process the materials taught in a useful manner, applying their knowledge in various context. This helps shape students' perception by the subject and provides practical applications, boosting critical thinking as well.…”
Section: Discussionmentioning
confidence: 98%
“…To address this challenge, educators increasingly turn to innovative instructional approaches such as taskbased learning, prioritizing active participation, problem-solving, and practical application in the learning process. Task-based learning, on the other hand, capitalizes on active engagement, promoting critical thinking and linking theoretical knowledge to real-world scenarios (Khoshsima & Shokri, 2016;Mäkiö & Mäkiö, 2023;Marashi & Mirghafari, 2019;Rodríguez et al, 2014). Students may better grasp Mendelian genetics patterns by incorporating innovative teaching approaches that simulate genetic crosses, phenotypic outcomes, and inheritance probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking is the ability to analyze and evaluate information objectively and independently [59][60][61]. Thus, critical thinking is a fundamental skill for navigating the complexities of environmental challenges.…”
Section: Introductionmentioning
confidence: 99%